Containers and doses of controlled release fertilizer in the production of radish in a protected environment - Viana, Caris; Marcelo de Almeida Guimarães; Santiago Rubio Ruiz; Ana Régia Alves de Araújo Hendges; Lemos Neto, Hozano de Souza; Tello, Jean Paulo de Jesus (Comunicata Scientiae, 2023)
Radish cultivation has aroused the interest of agricultural producers, but it is still necessary to improve management practices that allow greater production and quality of tubers. In this sense, the objective of this work was to evaluate the growth and production of radishes grown in containers of different volumes, filled with an environment enriched with increasing doses of controlled authorization fertilizer (LCA), in a greenhouse. The research was carried out in the Didactic Garden of the Federal University of Ceará. The experimental design used was in randomized blocks, in a split-plot scheme, with three replications. The plots were constituted by the volumes of containers (31 and 100 cm3.cell-1) and as subplots by the fertilization rates (0, 4, 8, 12 kg.m-3 or g.L-1). The number of leaves, shoot height, shoot fresh and dry mass, leaf area, chlorophyll 'a' and 'b', tuber length and diameter, tuber fresh and dry mass and total production per area were evaluated. . Plants grown in a 100 cm3 container showed higher values ​​for all variables and the controlled metering doses of fertilizer resulted in an increase in radish growth and production. It is concluded that it is possible to grow radish in containers filled with ALC-enriched substrate under screen-type protection conditions.